PENERAPAN PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DI SMAN 1 DARUL IMARAH ACEH BESAR - Nuralam Nuralam; Eliyana Eliyana (Jurnal Ilmiah Didaktika, 2017)
Problem solving, as the high mental activity in tackling mathematical problem should be a main concern to all respected parties. Facts and data in the field show students face a hard situation in solving math problems. Therefore, it requires an alternative solution to optimize student’s problem-solving capacity, one of them through scientific approach. Moreover, this approach builds student’s competencies in solving math problem through knowledge empowerment of critical thinking skills and creative thinking skills of students to solve the problems with a systematic and measurable way. In addition, the objectives of this research are (1) higher problem-solving skills, taught by scientific approach than those taught by realistic mathematical approach to trigonometric material, and (2) student’s response to problem solving ability through scientific approach on trigonometric material. The research population is all students of grade X SMAN 1 and the sample is the student who is in the grade X MIPA3 and grade IV MIPA by using cluster random sampling technique. This experimental study created by Posttest-only Control Design. This study also uses questionnaire and math problem solving test as the data collection. The result of research shows that (1) Statistical test of t-test on right side was obtained tcount 2,76 and ttable=1,65, and tcount > ttable then accept H1 reject H0 (2) Student response to approach 3,21. Thus, it is conclude that (1) the higher mathematical problem solving skills are taught through a scientific approach rather than the problem-solving skills taught by realistic mathematical approaches. (2) student’s response to the scientific approach of this category is very positive.